ANALYSIS AND RESULTS: CONFIRMATORY FACTOR ANALYSIS THE MALAY VERSION OF DREEM INVENTORY WITH MEDICAL STUDENTS OF UNISZA, KUALA TERENGGANU, MALAYSIA - Haque, Mainul; Yusoff, Muhamad Saiful Bahri; Majumder, Md. Anwarul Azim; Zulkifli, Zainal; Mohd Nasir, Farah Hanani Binti (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objectives: The DREEM inventory has been universally established as a generic instrument to assess health-related educational programs. There were some apprehensions regarding the psychometric properties of the DREEM raised in last few years. This study evaluated first ever the psychometric properties of the Bahasa Melayu version of the DREEM in a sample of Malaysian medical students. Methods: A cross-sectional study was carried and universal sampling method was applied. Researchers selected 1-5th-year medical students of Universiti Sultan Zainal Abidin, Malaysia, as study subjects. Researchers collected data through a guided self-administered questionnaire during a face-to-face session. Results: Confirmatory factor analysis (CFA) showed that the one factor model of DREEM-M (Model A), consisting 50 items were not fit, indicating it was a multidimensional instrument. On further CFA, it appeared that the proposed five-factor structure was not fit (Model B) as all the goodness-of-fit indices did not signify a model fit. Conclusions: The study findings revealed that the DREEM inventory 50-item inventory failed to achieve a model fit, but it demonstrated a high of internal consistency. The proposed 19-item DREEM-M revealed good model fit.